2011
DOI: 10.1016/j.ijheh.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Conclusions of the French Food Safety Agency on the toxicity of bisphenol A

Abstract: Since more than 10 years, risk assessment of bisphenol A (BPA) is debated at the international level. In 2008, the U.S. National Toxicology Program (NTP) expressed some concern for adverse effects, at current level of exposure to BPA, on developmental toxicity. In this context, the French Food Safety Agency (AFSSA) decided to review the toxicity data on BPA with a special focus on this endpoint at doses below 5mg/kg bw/day (the no observed adverse effect level set by different regulatory bodies). This paper su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…1,2 In the earlier study, residual amounts of BPA found in polycarbonate food contact articles ranged from 7 to 58 μg/g. 3 The European Commission established a migration limit of 600 μg/kg for BPA in plastic products that are intended for food-contact applications.…”
Section: ■ Introductionmentioning
confidence: 93%
“…1,2 In the earlier study, residual amounts of BPA found in polycarbonate food contact articles ranged from 7 to 58 μg/g. 3 The European Commission established a migration limit of 600 μg/kg for BPA in plastic products that are intended for food-contact applications.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Traditionally, one of the most commonly used coatings are epoxy-resins based in part on bisphenol A (BPA). BPA is a monomer that has been receiving much attention because of its possible effect as endocrine disruptor at lower doses [1,2]. However, recently, two independents agencies, such as Food and Drug Administration (FDA) and European Food Safety Authority (EFSA) independently reached the same conclusion, that BPA poses no health risk to consumers at the exposure concentrations in food [3] [4].In spite of these conclusions, consumers remain wary about the use of BPA in food contact materials.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicological profile of BPA was described in several reports of EFSA (2006EFSA ( , 2010, USA National Toxicology Program (NTP-CERHR, 2008), FAO/WHO (2010), ANSES (2011) and in several reviews (Arnich et al, 2011;Hengstler et al, 2011). EFSA opinions issued focused on the oral route of exposure, because it was found to be the most relevant for risk assessment of food/feed.…”
Section: Existing Assessmentsmentioning
confidence: 99%